Performance improvement tool for Thai make-to-order manufacturing - Wanitwattanakosol J. (2014)
This paper presents a framework to improve a performance of shop floor control for Thai make-to-order (MTO) small and medium enterprises (SMEs). Integrated definition for function modeling is exploited to explore activities and relate of components. In-depth interview with experts and practitioners in the case study is provided useful information. The empirical study is evaluated to suit for using the finalized SHEN model as a benchmark. Factor analysis is performed to find simplified information from variables. The data are collected from experience respondents by using a designed questionnaire. Each observed variable is assigned to test validity and reliability by factor loading and Cronbach's alpha, respectively. The results show that finalized SHEN can use as a performance improvement tool for Thai MTO SMEs. For example principle 11 is tested. Each observed variable has covariance value between 0.380-0.873. The value of reliability Cronbach's alpha for this factor is shown 0.869. Based on the scree plot, it is asserted that 5 observed variables are correctly formed in the same principle.